Electroacupuncture and vagus nerve stimulation are emerging therapies for hyperemesis gravidarum management - Zhang, Shike; He, Hui; Li, Xinyu; Guo, Yi (Frontiers in Neurology, 2025)
Hyperemesis gravidarum (HG), an extreme form of nausea and vomiting during pregnancy (NVP), significantly impairs the quality of life of affected individuals. This review examines the multifactorial etiology of the HG and evaluates the efficacy of non-traditional therapeutic approaches, namely, vagus nerve stimulation (VNS) and electroacupuncture. By synthesizing a comprehensive body of literature, we highlight the neurophysiological mechanisms underlying these therapies and propose a novel model for the HG management. The model focuses on vagus nerve modulation through targeted stimulation at the auricular and cervical points, suggesting a promising avenue for effective and safe treatment strategies against the NVP/HG.